Central Kalimantan Province's District and City Macroeconomics, Community Savings, and Economic Development - Framita Ester Sigiro; Alexandra Hukom; Benius Benius; Dicky Perwira Ompusunggu (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2023)
This study aims to determine and analyze the effect of Percapita Income, Inflation, Interest Rates and the Dependency Ratio on Total Public Savings and Economic Growth in Districts/Cities of Central Kalimantan Province. The method used in this study is path analysis with the help of the IBM SPSS Statistics version 26 program. Path analysis is a method used to determine the direct and indirect relationship between the independent variables and the dependent variable in the presence of a connecting variable. The data used in this study is a type of secondary data. Where these data are obtained from publications by the Central Statistics Agency (BPS) and Bank Indonesia (BI). The results of this analysis show that percapita income directly has a positive and significant effect on the amount of people's savings. Inflation directly has a negative and insignificant effect on the amount of public savings. Interest rates directly have a positive and insignificant effect on the amount of people's savings. The dependency ratio has a direct and significant negative effect on the amount of people's savings. Percapita income directly has a positive and insignificant effect on economic growth. Inflation has a direct and significant negative effect on economic growth. Interest rates have a direct and significant negative effect on economic growth. The dependency ratio directly has a negative and insignificant effect on economic growth. The amount of public savings has a direct and significant negative effect on economic growth. Per capita income does not directly affect economic growth through the amount of public savings. Inflation does not directly affect economic growth through the amount of public savings. Interest rates indirectly do not affect economic growth through the amount of public savings. The dependency ratio does not directly affect economic growth through the amount of public savings.